Modern sport and its implications: a look about the 61st Brazilian University Games (Impetus, 2021)
Knowledge of modern sport arises from the experiences provided by related events with this topic, it allows multiple reflections, taking into account that such a theoretical matrix allows to analyze the ruptures and continuities of this phenomenon in the context Social. In this perspective, this study carried out a report of experience about the 61st edition of the University Games Brazilians from JUBS, which took place from 24 to October 28, 2013 in Goiânia / GO, a municipality located in the center-west of Brazil. This study aimed elucidate the manifestations of modern sport through of the actions carried out during said event. Is about a qualitative exploratory study. The methodological procedure addressed in the field research was participant observation. In this context, we gave ourselves also account of the execution of the proposed activities, such as the technical day, the realization of matches of different modalities, scientific conferences, among others. Therefore, it was found that the characteristics of modern sport materialized at all times, through observation of streamlining activities, bureaucratization of games, as well as the quantification of the results. In this sense, it was concluded that this event contributes directly to the realization of instilled ideals In modern sport, Thus consolidation, reorganization of such a phenomenon in the academic space.